'Do Well B.': Design Of WELL Being monitoring systems. A study protocol for the application in autism. Issue 2 (20th February 2015) - Dutheil, Frédéric; Chambres, Patrick; Hufnagel, Cédric; Auxiette, Catherine; Chausse, Pierre; Ghozi, Raja; Paugam, Guillaume; Boudet, Gil; Khalfa, Nadia; Naughton, Geraldine; Chamoux, Alain; Mermillod, Martial; et al.
Abstract : Introduction: Individuals with autism spectrum disorder (ASD) have difficulties in communication and social interaction resulting from atypical perceptual and cognitive information processing, leading to an accumulation of anxiety. Extreme overloading experienced internally may not be externally visible. Identifying stressful situations at an early stage may avoid socially problematic behaviour from occurring, such as self-injurious behaviour. Activation of the autonomous nervous system (ANS) is involved in the response to anxiety, which can be measured through heart rate variability and skin conductance with the use of portable devices, non-intrusively and pain-free. Thus, developing innovative analysis of signal perception and reaction is necessary, mainly for non-communicative individuals with autism. Methods and analysis: The protocol will take place in real life (home and social environments). We aim to associate modifications of the ANS with external events that will be recorded in a synchronous manner through a specific design (spy glasses with video/audio recording). Four phases will be carried out on ASD participants and aged-matched controls: (1) 24-hour baseline pre-experiment (physical activity, sleep), (2) 2 h in a real life situation, (3) 30 min in a quiet environment, interrupted by a few seconds of stressful sound, (4) an interview to record feelings about events triggering anxiety. ASD and control participants will be together for phases 2 and 3, revealing different physiological responses to the same situations, and thus identifying potentially problematic events. The novelty will be to apply time-series analyses (which led to several Nobel Prizes in quantitative finance) on ANS series (heart rate, heart rate variability, skin conductance) and wrist motion. Ethics and dissemination: Ethical approval has been obtained from Ethics Committee of Clermont-Ferrand (South-East I), France (2014-A00611–46). Trial findings will be disseminated via open-access peer-reviewed publications, conferences, clinical networks, public lectures and our websites. Trial registration number: ClinicalTrials identifier NCT02275455 .